Hepatocyte Growth Factor-Preconditioned Neural Progenitor Cells Attenuate Astrocyte Reactivity and Promote Neurite Outgrowth - Hong, James; Dragas, Rachel; Khazaei, Mohammad; Ahuja, Christopher S.; Fehlings, Michael G. (Frontiers in Cellular Neuroscience, 2021)
The astroglial scar is a defining hallmark of secondary pathology following central nervous system (CNS) injury that, despite its role in limiting tissue damage, presents a significant barrier to neuroregeneration. Neural progenitor cell (NPC) therapies for tissue repair and regeneration have demonstrated favourable outcomes, the effects of which are ascribed not only to direct cell replacement, but trophic support. Cytokines and growth factors secreted by NPCs aid in modifying the inhibitory and cytotoxic post-injury microenvironment. In an effort to harness and enhance the reparative potential of NPC secretome, we utilized the multifunctional and pro-regenerative cytokine, hepatocyte growth factor (HGF), as a cellular preconditioning agent. We first demonstrated the capacity of HGF to promote NPC survival in the presence of oxidative stress. We then assessed the capacity of this modified conditioned media (CM) to attenuate astrocyte reactivity and promote neurite outgrowth in vitro. HGF pre-conditioned NPCs demonstrated significantly increased levels of tissue inhibitor of metalloproteinases-1 and reduced vascular endothelial growth factor compared to untreated NPCs. In reactive astrocytes, HGF-enhanced NPC-CM effectively reduced glial fibrillary acidic protein expression and chondroitin sulphate proteoglycan deposition to a greater extent than either treatment alone, and enhanced neurite outgrowth of co-cultured neurons. In vivo, this combinatorial treatment strategy might enable tactical modification of the post-injury inhibitory astroglial environment to one that is more conducive to regeneration and functional recovery. These findings have important translational implications for the optimization of current cell-based therapies for CNS injury.